2020
DOI: 10.1101/2020.04.11.037093
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

BIP4COVID19: Releasing impact measures for articles relevant to COVID-19

Abstract: Since the beginning of the 2019-20 coronavirus pandemic, a large number of relevant articles has been published or become available in preprint servers. These articles, along with earlier related literature, compose a valuable knowledge base affecting contemporary research studies or, even, government actions to limit the spread of the disease and treatment decisions taken by physicians. However, the number of such articles is increasing at an intense rate making the exploration of the relevant literature and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Not only does each DOI carry a cost (which is currently born by CERN, which hosts and manages Zenodo), in cases where there are 10 multiple versions, an excessive number of documents can make it difficult for readers and users to navigate which version they should cite. As one example, Vergoulis et al (2021a), which is a dataset, carries one DOI (10.5281/zenodo.3723281), the website claims that there are 78 versions, but the latest version is indicated 11 as being version #70 (December 5, 2021), and all indicated versions have different DOIs. Moreover, on the 12 same page, the preprint is indicated with two separate citations, the first to Zenodo (Vergoulis et al, 2021a), and the second to bioRxiv, which is a preprint server (Vergoulis et al, 2021b).…”
Section: Strengths and Weaknesses Of The Doi And Competing Data Stora...mentioning
confidence: 99%
See 2 more Smart Citations
“…Not only does each DOI carry a cost (which is currently born by CERN, which hosts and manages Zenodo), in cases where there are 10 multiple versions, an excessive number of documents can make it difficult for readers and users to navigate which version they should cite. As one example, Vergoulis et al (2021a), which is a dataset, carries one DOI (10.5281/zenodo.3723281), the website claims that there are 78 versions, but the latest version is indicated 11 as being version #70 (December 5, 2021), and all indicated versions have different DOIs. Moreover, on the 12 same page, the preprint is indicated with two separate citations, the first to Zenodo (Vergoulis et al, 2021a), and the second to bioRxiv, which is a preprint server (Vergoulis et al, 2021b).…”
Section: Strengths and Weaknesses Of The Doi And Competing Data Stora...mentioning
confidence: 99%
“…As one example, Vergoulis et al (2021a), which is a dataset, carries one DOI (10.5281/zenodo.3723281), the website claims that there are 78 versions, but the latest version is indicated 11 as being version #70 (December 5, 2021), and all indicated versions have different DOIs. Moreover, on the 12 same page, the preprint is indicated with two separate citations, the first to Zenodo (Vergoulis et al, 2021a), and the second to bioRxiv, which is a preprint server (Vergoulis et al, 2021b). On that Zenodo page, it is indicated that Vergoulis et al (2021a) is a supplement of version 2 of the Vergoulis et al (2021b) bioRxiv preprint.…”
Section: Strengths and Weaknesses Of The Doi And Competing Data Stora...mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, with regard to Research Impact Assessment, Vergoulis, Kanellos, Chatzopoulos, Karidi, and Dalamagas (2021) introduce BIP4COVID19, an open dataset that offers a variety of impact measures for coronavirus-related scientific articles. These measures can be exploited for the creation or extension of added-value services aiming to facilitate the exploration of the respective literature.…”
Section: Contributions To the Special Issuementioning
confidence: 99%